The ambiguous pruritogenic role of interleukin-31 in cutaneous T-cell lymphomas in comparison to atopic dermatitis: a review - Olszewska, Berenika; Sokołowska-Wojdyło, Małgorzata; Lakomy, Joanna; Nowicki, Roman (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2020)
Cutaneous T-cell lymphomas (CTCLs) comprise a group of chronic heterogeneous diseases of unknown pathogenesis, characterized by non-specific skin lesions such as patches, plaques and tumours. CTCL is accompanied by persistent pruritus poorly responding to antihistamines and therefore significantly reducing quality of life in patients with lymphomas. According to research data, interleukin-31 (IL-31) contributes to initiation and maintenance of the inflammatory process of the skin and pruritus in inflammatory dermatoses such as atopic dermatitis (AD), which is well established. The studies of a similar role of IL-31 in CTCLs are less homogenous. Due to contradictory reports concerning IL-31 and CTCL we have analysed available literature to summarize its role, focusing on CTCL and AD.